TÄrikh al-Maâ€™had al-TurÄthÄ« wa ThaqafÄtuhu - Mas'ud, Abdurrahman (Studia Islamika, 2000)
Within the Indonesian context, the history of pesantren cannot be alienated from that of Walisongo (The Nine Saint), who were said to be responsible for the spread of Islam in Java in the 16th-17th centuries. Maulana Malik Ibrahim (died 1419), the "spiritual father" of the Walisongo, is usually considered by the santri comntunity in Java to be "the teacher of the teachers" of the pesantren tradition. Some of the well-known pesantrens in Java, claim that they received their inspiration from the dakwah (ie.Islamic propagation) of Maulana Malik lbrahim. Moreover, oral histories indicate that old and influential pesantrens outside of Java -such as Nahdlatul Watan, established in 1934 in East Lombok NTB and now home for about 10,000 santris scattered throughout its branches- also had Inspiration from the Walisongo teaching. This, in turn, has made Maulana Malik lbrahirn as the father of the Walisongo even more well-know.DOI:Â 10.15408/sdi.v7i1.718